Clinical characteristics and outcome of infective endocarditis due to Abiotrophia and Granulicatella compared to Viridans group streptococci. Issue 2 (August 2022) - Téllez, Adrián; Ambrosioni, Juan; Hernández-Meneses, Marta; Llopis, Jaume; Ripa, Marco; Chambers, Stephen T.; Holland, David; Almela, Manel; Fernández-Hidalgo, Núria; Almirante, Benito; Bouza, Emilio; Strahilevitz, Jacob; et al.
Highlights: Clinical features and outcomes of Abiotrophia and Granulicatella IE are similar. Patients with Abiotrophia / Granulicatella are younger than viridans streptococci IE. Rate of surgery between Abiotrophia / Granulicatella and Viridans IE is similar. Survival between Abiotrophia / Granulicatella and Viridans IE is similar. Summary: Objective: To describe the clinical characteristics and outcome of Abiotrophia and Granulicatella infective endocarditis and compare them with Viridans group streptococci infective endocarditis. Methods: All patients in the International Collaboration on Endocarditis (ICE) - prospective cohort study (PCS) and the ICE-PLUS cohort were included ( n  = 8112). Data from patients with definitive or possible IE due to Abiotrophia species, Granulicatella species and Viridans group streptococci was analyzed. A propensity score (PS) analysis comparing the ABI/GRA-IE and VGS-IE groups according to a 1:2 ratio was performed. Results: Forty-eight (0.64%) cases of ABI/GRA-IE and 1, 292 (17.2%) VGS-IE were included in the analysis. The median age of patients with ABI/GRA-IE was lower than VGS-IE (48.1 years vs. 57.9 years; p  = 0.001). Clinical features and the rate of in-hospital surgery was similar between ABI/GRA-IE and VGS-IE (52.1% vs. 45.4%; p  = 0.366). Unadjusted in-hospital death was lower in ABI/GRA-IE than VGS-IE (2.1% vs. 8.8%; p  = 0.003), and cumulative six-month mortality was lower in ABI/GRA-IE than VGS-IE (2.1% vs. 11.9%; p <0.001). After PS analysis, in-hospital mortality was similar in both groups, but six-month mortality was lower in the ABI/GRA IE group (2.1% vs. 10.4%; p  = 0.029). Conclusions: Patients with ABI/GRA-IE were younger, had similar clinical features and rates of surgery and better prognosis than VGS-IE. Graphical abstract: Survival curves according to Abiotrophia/Granulicatella infective endocarditis (ABI/GRA-IE) or Viridans group streptococci infective endocarditis (VGS-IE). Image, graphical abstract